Problematika Penerjemahan Arab-Indonesia - Maulana, Muhamad Aqil (Al Ibrah: Journal of Arabic Language Education, 2022)
The background of this research is the quality of the Arabic-Indonesian translation which has experienced various problems, such as unacceptable, unreadable, and inaccurate. This study aims to find the problems of Arabic-Indonesian translation that often occur and provide solutions. The research method uses a qualitative-descriptive method. From this research, there are six problems that often occur in the translation process, namely: 1) Interference problems in translation; 2) cultural vocabulary and metaphors; 3) transliteration problems; 4) morphological problems; 5) syntax problems; and 6) idiomatic problems. The conclusions from this study are: 1) Problems are translation problems, namely mistakes that are often experienced by translators in the translation process; and 2) The discovery of the six problems in Arabic-Indonesian translation as previously mentioned.